EVALUATION OF THE EFFECTIVENESS OF DIGITAL TECHNOLOGIES IN DENTAL IMPLANT PROSTHETICS - Rixsiyeva Dildora Ulug’bek qizi,; Temirova Nazokat G’olib qizi,; Xaitboyeva Mohirabonu Otkir qizi,; Musabekova Azizabonu Azamat qizi, (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2026)
The article discusses the current possibilities and effectiveness of using digital technologies in prosthetic dentistry for dental implant prosthetics. It analyzes the main stages of the digital workflow, including intraoral scanning, virtual planning, and the use of CAD/CAM systems in the manufacture of prosthetic structures. Particular attention is paid to the influence of digital methods on the accuracy of prosthesis fit, functional stability of implants, aesthetic indicators, and clinical predictability of treatment. The advantages of digital technologies over traditional methods are discussed, as well as factors limiting their effectiveness in clinical practice.